2013
DOI: 10.4236/jmmce.2013.11001
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Heat-Treated NST 37-2 Steel in Hydrochloric Acid Solution

Abstract: Corrosion of metal components constitutes a major challenge in many engineering systems, with appropriate design, proper material selection, and heat treatment as commonly used control strategies. In this study, the corrosion behaviour of heat-treated (annealed, normalised, hardened, and tempered) NST 37-2 steel in three concentrations (1.0, 1.5 and 2.0 M) of hydrochloric acid solution was investigated using weight loss and electrode-potential methods. Results showed that corrosion rate increased with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[13][14][15][16] For stainless steel, promising outcomes have been achieved with extracts from Salvia officinalis leaves and khillah. [17,18] These plant-based solutions are not only costeffective and readily available but also renewable. [19,20] In the pursuit of novel eco-friendly corrosion inhibition strategies, this study investigates the potential of (DS) plant extract as a corrosion inhibitor for concrete steel exposed to a highly corrosive 1 M H 2 SO 4 environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] For stainless steel, promising outcomes have been achieved with extracts from Salvia officinalis leaves and khillah. [17,18] These plant-based solutions are not only costeffective and readily available but also renewable. [19,20] In the pursuit of novel eco-friendly corrosion inhibition strategies, this study investigates the potential of (DS) plant extract as a corrosion inhibitor for concrete steel exposed to a highly corrosive 1 M H 2 SO 4 environment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed the remarkable corrosion inhibition potential of extracts from sources such as coffee, garlic husks, fruit peels, Ilex paraguariensis, and Poinciana pulcherrima, particularly against HCl‐induced corrosion in carbon steel [13–16] . For stainless steel, promising outcomes have been achieved with extracts from Salvia officinalis leaves and khillah [17,18] . These plant‐based solutions are not only cost‐effective and readily available but also renewable [19,20] …”
Section: Introductionmentioning
confidence: 99%
“…Demirkol et al [11] investigated the case depth of carburized steel on fatigue performance. T. G. Fadara et al [12] observed the corrosion resistance of carburized steel in hydrochloric acid services. The works carried out by researchers in the past are effective.…”
Section: Introductionmentioning
confidence: 99%
“…Their resistance is determined by their passivation characteristics, elemental composition, heat treatment and the corrosive medium. The durability of the protective covering on stainless steels is subject to its self-healing ability (Fadare and Fadara, 2013;Kempester, 1984). The film collapses when the rate of corrosion is much faster than the reforming rate leading to severe localized corrosion attack and eventually catastrophic failures.…”
Section: Introductionmentioning
confidence: 99%